The autonomy of adolescents in relation to the direct of immunization against sexually transmitted infections: bibliographic review - Gomes de Lima, Alessandre; Lima da Costa, Ruth Silva; Gonçalves, Thiago Gomes; Lima de Souza, Paola; Aguiar, Valéria da Silva; Lima da Silva, Thais; Ribeiro, Ianca; Ferreira, Fábio Reis; Lobato, Cirley Maria de Oliveira; Ribeiro, Dilza Terezinha Ambros; Nunes, Rui Manuel Lopes (Acta Bioethica, 2023)
The present study is an analysis of the literature on the bioethical aspect of autonomy in relation to immunization against Hepatitis B and HPV in adolescence. A bibliographic review was carried out based on the prism method, which included articles in Portuguese and English which were searched on the Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and the National Library of Medicine (PUBMED), using the following descriptors Hepatitis B Vaccines, bioethics, Humans. The results demonstrated the efficiency of health professionals in contacting the individual and convincing him/her through an open dialogue and creation of bonds. It was also evidenced the study evidenced the patient's right to progressive autonomy, in which he gains the right to some choices such as immunizations of sexually transmitted diseases, such as Hepatitis B and HPV, however it is necessary for the adolescent to be educated about immunization. Therefore, the adolescent's right to progressive autonomy is recognized, regarding the choice of immunizations against Hepatitis B and HPV, however, it must be considered that these individuals are instructed on the individual and/or collective benefits of vaccination, contemplated by health education activities by qualified professionals, aiming to expand the global coverage of immunization with diseases that characterize public health problems.